Web-Based Scada System For Power System State Estimation - Maryam Khirul Annuar, Maryam (2010)
For Power System, in order to perform accurate and reliable analysis for a computer-aided tool that controls and monitors the performance of the power utility’s transmission and generation system called the Energy Management System (EMS) [1], dependable and accurate data are required.